Phytochemical screening and in vitro anticancer activity of ethyl acetate fraction of seagrass Halodule uninervis from Mandapam coastal region, Rameswaram, Gulf of Mannar, India (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Seagrasses are one of the groups of marine angiosperms widely distributed all over the coastal regions. The seagrass ecosystem is very productive and traditionally used for a variety of therapeutic purposes. The present study aimed to investigate the in-vitro anticancer activity against malignant melanoma (A375), lung carcinoma (A549), cervix adenocarcinoma (HeLa) and colorectal adenocarcinoma (HT29) cell lines and phytochemical screening of ethyl acetate fraction of Halodule uninervis (EAF) from Mandapam coastal region, Rameswaram, Gulf of Mannar, India. The qualitative phytochemical analysis of EAF was performed as followed by standard methods. EAF showed the presence of alkaloids, steroids, terpenoids, flavonoids, phenols and quinones. The total flavonoid and phenolic contents of EAF were determined using the spectrophotometric method. The total flavonoid and phenolic contents showed 67.33 ± 1.52 mg QE/g dried fraction and 87.75 ± 1.39 mg GAE/g dried fraction, respectively. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of EAF shows the presence of 23 phytochemical compounds. The in-vitro anticancer activity of EAF was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, AO/EtBr staining and DNA fragmentation assay for 24 hours treatment. The IC50 values of EAF showed 91.64 ± 1.61 μg, 269.16 ± 5.17 μg, 845.16 ± 36.09 μg and >1000 μg against A549, HeLa, HT29 and A375 cells, respectively. Followed by reference standard, Doxorubicin showed IC50 values of 17.53 ± 0.07 μg, 14.12 ± 0.30 μg, 17.44 ± 0.25 μg and 21.44 ± 0.40 μg against A549, HeLa, HT29 and A375 cells, respectively. AO/EtBr and DNA fragmentation assay confirmed the occurrence of apoptosis in the A549 cell line after the treatment of EAF. These results suggest that H. uninervis is a promising source of cytotoxicity against A549 cells and could be considered as a source for new lead structures to the development of new anticancer drugs.